Credit allocation, risk management and loan portfolio performance of MFIs—A case of Ugandan firms - Bob Ssekiziyivu; Rogers Mwesigwa; Mayengo Joseph; Isaac Nkote Nabeta (Cogent Business & Management, 2017)
Purpose: The purpose of this study was to establish examine the relationship between credit allocation, risk management and loan portfolio performance of MFIs in Uganda. Design/methodology/approach: A cross-sectional research design was adopted which involved descriptive, correlation and regression approaches. Data were analysed through SPSS. Simple random sampling was used to select a sample of 40 MFIs from the population of 45 in Kampala and Wakiso districts. Findings: Results indicated that credit allocation and risk management had a significant relationship with loan portfolio performance. Results from the regression analysis showed that credit allocation and risk management significantly predicted 23.9% of loan portfolio performance. Practical implications: It was recommended that managers of the MFIs should conduct pre-disbursement trainings through workshops and seminars for all successful loan applicants which would enable them on how to utilize the loan facilities acquired which will eventually reduce on the default rates. Originality/value: This is one of the few studies that focus on credit allocation, risk management and loan portfolio performance of MFIs within the context of Uganda.
Keywords: 650